Endogenous trade policy: Political struggle in the growth process - Yoshiaki Sugimoto (Osaka University, Institute of Social and Economic Research (ISER), 2006)
This paper develops a dynamic theory that accounts for the evolution of trade policy, underlying internal class conflicts, and output growth performance over the last few centuries. By analyzing political responses to the distributional effects of international trade, it finds a prominent interaction between trade policy and the pattern of economic development, and also a significant role for trade liberalization in economic take-off. Consistent with historical evidence for Western Europe, land-scarce economies reach a developed stage through the ebb and flow of liberalism. In contrast, land-abundant countries tend to stagnate because of landlords' opposition to industrialization.
Keywords: F10; F13; F43; O11; O40; 330; Trade Policy; Growth; Class Conflict